Late-Holocene climatic change recorded in sediment cores from Ellis Fjord, eastern Antarctica - Andrew McMinn; Heijnis, H; Harle, K; McOrist, G (2001)
An analysis of diatom assemblages, Total Organic Carbon (TOC), carbon-nitrogen ratio, Î´13C, biogenic silica and carbonate in two marine sediment cores from Ellis Fjord, eastern Antarctica, reveals episodes of climatic change at 3600, 2500, 2000 and 1000 yr BP. Using the diatom data, principal component analysis, the fast-ice index (FI), benthic index (BI) and snow index (SI) (which are derived from the diatom data), a period of reduced temporal sea-ice cover is identified prior to 2500 BP. There was a large increase in sea-ice extent between 2500 and 2000 BP followed by a smaller decline. Temporal sea-ice extent after 2000 BP was still significantly greater than prior to 2500 BP. Both cores were taken from anoxic basins within the fjord. It was found that the better preservation allowed the recognition of taxa such as Chaetoceros vegetative cells, which are not usually preserved. This enabled the distinction between ice-edge blooms, dominated by Fragilariopsis curta, and open-water blooms dominated by Chaetoceros. Even though Watts Basin receives a significant summer meltwater input each year, it has not been possible to recognize this signal in the sediment core.